The Relationship Between Social Support and Anxiety Levels in Breastfeeding Mothers in Luwu District - Jasadin, Nurul Ainun; Syafar, Muhammad; Riskiyani , Shanti; Fajarwati1d, Indra; Nurzakiyah, Nurzakiyah (Journal of Neonatal Surgery, 2025)
BACKGROUND: The breastfeeding period is a vulnerable time for mothers, with increased risk of mental health issues such as anxiety and depression. One way to reduce anxiety in breastfeeding mothers is through social support from those closest to them. Objective: This study aims to examine the relationship between social support and anxiety levels among first-time breastfeeding mothers. METHODS: This quantitative study used a cross-sectional design. The population consisted of 114 first-time breastfeeding mothers from three public health center areas in Luwu Regency. Total sampling was used to select participants. Data were collected using two questionnaires: a social support questionnaire adapted from the Hughes Breastfeeding Support Scale and the Hamilton Anxiety Rating Scale (HARS) for anxiety. RESULTS: The findings showed significant relationships between informational support (p = 0.004), instrumental support (p = 0.003), and emotional support (p = 0.000) with anxiety levels in breastfeeding mothers. However, no significant relationship was found between appraisal support and anxiety (p = 0.77). CONCLUTION: Social support is significantly associated with anxiety levels among first-time breastfeeding mothers and plays an important role in supporting the success of exclusive breastfeeding.